So you want to start a side hustle : build a business that empowers you to live your life, your way - Bohlig, Carrie; Clickner, Craig (McGraw Hill, 2021)
"Create a successful side hustle that pays off in a life changing way with this definitive guide from two expert side hustlers. Have you ever dreamed of a way to earn extra money, cover unexpected expenses, or step away from a corporate job and create a life that's more in line with what you truly value? If so, the idea of the "side hustle" could be more relevant to you than ever. In this hard-hitting guide, a husband-and-wife team who have built multiple million-dollar side hustles lets you in on the secrets of how they finally said goodbye to their corporate life to become full-time parents and part-time entrepreneurs. Many people get stuck in the thinking or planning stages of starting a side hustle instead of actually generating revenue. Carrie Bohlig and Craig Clickner stop this from being your reality and take the process to the next level with actionable steps that will help you establish a clear vision-the why; find the right associations and mentorship-the who: implement the proper systems-the how; and develop the right foundation for ongoing success-the Lifeset. By applying these foundational components, you'll immediately begin to build something that can radically change your life. Filled with a wealth of real-life stories, personal wins and losses, and anecdotes about the authors' experiences traveling the globe to speak in front of 25,000 people annually, you will be inspired and ready to believe in your ideas and put them into action"--